If it's not what You are looking for type in the equation solver your own equation and let us solve it.
57x=8(7x-2)
We move all terms to the left:
57x-(8(7x-2))=0
We calculate terms in parentheses: -(8(7x-2)), so:We get rid of parentheses
8(7x-2)
We multiply parentheses
56x-16
Back to the equation:
-(56x-16)
57x-56x+16=0
We add all the numbers together, and all the variables
x+16=0
We move all terms containing x to the left, all other terms to the right
x=-16
| 5a+4a+2a-8a+a=12 | | 2x/6-2/15=2x/9+1/6 | | 13u-12u=8 | | 32^d-2=10 | | 9x=8(x+2) | | 6h-4h=12 | | 7j-2j=20 | | 3x-8=6x=9 | | 2y/3-1/6=7/2 | | 3x+-15=x+7 | | 3x+-15=x7 | | -8=-14x | | (3-3k)^2-4(7k+2)=0 | | -10x+90=80 | | 2•x+8=4•x | | -3x^2+5x-8=0 | | 2•x+13=4•(x+3)+2 | | 4x+8=(-28)-2x | | (3-3k)(3-3k)=0 | | 8-4p-12=52 | | 4x+2+x=-3+2x | | 2(4x+1)=+3(x+2) | | 8=y/3-7 | | 175m-125m+43,640=45,450-175m | | 3u+4=13 | | -u+225=278 | | 97=271-u | | (2x-25)=(3x-10) | | 1-4x+12=0 | | -4+⅔x=x/6-½ | | 6(5x+7)-9x=105 | | x/4=3=9 |